2012
DOI: 10.1130/ges00728.1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Volcanic rock and mantle xenolith compositions in the Sierra Nevada (western United States) contradict a commonly held view that continental crust directly overlies asthenosphere beneath the Sierran range front, and that ancient continental mantle lithosphere (CML) was entirely removed in the Pliocene. Instead, space-time trends show that the Walker Lane is the principle region of mantle upwelling and lithosphere removal in eastern California, that lithosphere loss follows the migration of the Mendo cino Tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 152 publications
(231 reference statements)
3
30
0
Order By: Relevance
“…Each age group shows evidence for hybridization of mantle lithosphere and depleted mantle source components, with local increase of depleted mantle components eastward with time (Van Kooten, 1981;Ducea and Saleeby, 1998a;Farmer et al, 2002;DePaolo and Daley, 2000;Blondes et al, 2008;Putirka et al, 2012). The depth of melt extraction decreases with time from ~100-125 km to ~40-75 km, and fi nally into the lower felsic crust for silicic members (Van Kooten, 1980;Ducea andSaleeby, 1996, 1998a;Putirka et al, 2012). Figure 1 shows the areas over which the ca.…”
Section: Model Predictions For Volcanism Heat Flow and Seismicitymentioning
confidence: 96%
See 1 more Smart Citation
“…Each age group shows evidence for hybridization of mantle lithosphere and depleted mantle source components, with local increase of depleted mantle components eastward with time (Van Kooten, 1981;Ducea and Saleeby, 1998a;Farmer et al, 2002;DePaolo and Daley, 2000;Blondes et al, 2008;Putirka et al, 2012). The depth of melt extraction decreases with time from ~100-125 km to ~40-75 km, and fi nally into the lower felsic crust for silicic members (Van Kooten, 1980;Ducea andSaleeby, 1996, 1998a;Putirka et al, 2012). Figure 1 shows the areas over which the ca.…”
Section: Model Predictions For Volcanism Heat Flow and Seismicitymentioning
confidence: 96%
“…3A, 3B), and geochemical data indicating that basaltic rocks erupted during and following lithosphere removal contain substantial continental lithosphere components (cf. Putirka et al, 2012). Our preferred model predicts complex regional interlayering of ascended asthenosphere, mobilized mantle lithosphere, delaminated root, and entrained lower felsic crust, as well as compressed isotherms that migrate across the layering as it develops.…”
Section: Model Predictions For Volcanism Heat Flow and Seismicitymentioning
confidence: 98%
“…In Putirka et al (2012), it was shown that K 2 O contents are a key discriminator between Cascade and Basin and Range magmas; the latter group tends to have higher K 2 O contents at any given SiO 2 content. Furthermore, in Putirka and Busby (2007) it was suggested that high K 2 O contents may signal high crustal extension rates.…”
Section: Introductionmentioning
confidence: 98%
“…Whether mantle processes play an active role in promoting volcanism (e.g., a mantle plume; Wang et al, 2002) or magmatism is a passive response to tectonism and crustal extension (McQuarrie and Oskin, 2010) is a fundamental issue of Cordilleran evolution. To test whether plate tectonic actions control volcanism, we add a geochemical perspective to structural and palinspastic reconstructions of Snow and Wernicke (2000), McQuarrie and Wernicke (2005), and McQuarrie and Oskin (2010), and test the models in Putirka et al (2012) using a broader context. We do this by comparing temporal distributions and chemical compositions of volcanic rocks to time-space patterns of extensional deformation (Snow and Wernicke, 2000; McQuarrie and Wernicke, 2005) and an evolving plate boundary (Atwater and Stock, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation